Tobacco Control Politics in Indonesia: Regional and Global Perspective - Paksi, Arie Kusuma; Prasetyoningsih, Nanik; Sugiyo, Dianita (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2019)
The study examines tobacco control policies of Indonesia, national and international players, the role of political elite and social demography of smoking. The analysis explains the relation of national and international players associated with the tobacco industry, interest of local community, structural and political powers that limit the legislation on tobacco control. The current situation of smoking and tobacco use in the social system of Indonesia is alarming. Indonesia is the working ground of different multinational brands that have industries and production units of cigarettes. The economic perspectives of the tobacco industry involvement of government and political powers in this industry make it more complex. The study is based on qualitative sources that are evaluated for the tobacco industry and its implications on Indonesian society. The results provide a comprehensive overview of the tobacco industry and the role of different actors that can be regularized by imposing strict legislation. The study also provides recommendations to manage the tobacco industry that will guide the corrective path of reducing tobacco culture in the society.